Apakah Sadd adz-Dzari’ah Menjadi Metode Paling Tepat dalam Beristinbat di Masa Pandemi - Rizka, Rizka; Bakhtiar, Arova (Prosiding University Research Colloquium, 2021)
The pandemic that occurred since 2019 caused a disruptive change in the pattern of humanlife demands the productivity of fatwas related to new things. This study aims to look moredeeply at the sadd adz-dzari'ah method and its correlation in determining fatwas duringthe pandemic. The method used in this study is a qualitative method by holisticallyanalyzing the object of research. The results of the study found that sadd adz-dzari'ah hasa very important position in the process of determining the fatwa by Fatwa Council inIndonesia and become the most appropriate method for preventing mudhorot andachieving maslahah.